THE SERVICE LIFE of IMPLANT-RETAINED OVERDENTURE ATTACHMENT SYSTEMS - Pigozzo, Monica Nogueira; Mesquita, Marcelo Ferraz; Pessanha Henriques, Guilherme Elias; Vaz, Luis Geraldo [UNESP] (Mosby-elsevier, 2009)
Statement of problem. Implant-retained overdentures are a treatment option for patients who are not satisfied with conventional complete dentures. Although implant-retained overdentures are widely used, little data are available or provided by implant manufacturers about retentive strength and wear of attachments.Purpose. The purpose of this study was to evaluate retentive strength and fatigue resistance of 4 overdenture bar-and-clip attachment systems.Material and methods. Forty bar-and-clip attachment system specimens were tested (n=10): Conexao Bar Clip (polymer clip), Sterngold Hader Bar (polymer clip), 3, Gold Hader Type Clip (metal clip), or SIN Clipo (metal clip). Specimens immersed in artificial saliva were tested to 5500 cycles at 0.8 Hz using a servohydraulic universal testing machine. Retention strength values (N) were recorded initially and after 1100, 2200, 3300, 4400, and 5500 insertion and removal cycles during the tensile test using a speed of I mm/min and a load cell of 1 kN. Data were submitted to a 2-way repeated-measures ANOVA and the Tukey A post hoc test (alpha=.05).Results. An increase in retention strength values was observed during the fatigue test after 5500 cycles of insertion and removal. No significant difference in retentive strength was observed in the groups using polymer clips (Conexao Bar Clip and Sterngold Hader Bar) (P=.729); the same occurred with metal clip systems (SIN Clipo and 31 Gold Hader Type Clip) (P=.068). The SIN Clipo system demonstrated the smallest retention strength values, which were significantly different from the other 2 attachment systems, the Sterngold Hader Bar (P<.01) and the Conexao Bar Clip (P<.01). Although the 31 Gold Hader Type Clip did not differ significantly, in terms of retentive strength, from the Sterngold Hader Bar (P=.258), its retentive strength was significantly lower than the retentive strength of the Conexao Bar Clip system (P=.030).Conclusions. The systems evaluated demonstrated satisfactory retention for all time periods tested, as retention strengths from 5 to 7 N should be sufficient to stabilize overdentures. No component fracture or compromise in retention was found for any of the systems tested. (J Prosthet Dent 2009;102:74-80)